Pengaruh Kepemilikan Institusional, Profitabilitas, Likuiditas, dan Solvabilitas terhadap Nilai Perusahaan Asuransi yang Terdaftar di BEI - Shafa Sabitananda Afifah; Sri Purwaningsih (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze institutional ownership, profitability, liquidity, and solvency on company value in insurance companies listed on the Indonesia Stock Exchange for the period 2019-2024. The research method uses a quantitative approach with a causal design and uses secondary data from financial reports officially published by the IDX (www.idx.co.id) with data processing assisted by SPSS version 25. Company value is measured using price book value (PBV), institutional ownership is described by the percentage of institutional share ownership, profitability is measured by return on assets (ROA), liquidity by the current ratio (CR), and solvency by the debt to equity ratio (DER). The results of the study indicate that institutional ownership and profitability do not have a significant effect on company value. However, liquidity and solvency have a significant effect on company value. In conclusion ,indicates that investors in the insurance sector consider the company's ability to maintain financial stability and capital structure more than ownership structure and profits in determining company value